2021
DOI: 10.1039/d1ra04281e
|View full text |Cite
|
Sign up to set email alerts
|

Elevated electrochemical performances enabled by a core–shell titanium hydride coated separator in lithium–sulphur batteries

Abstract: A TiO2−x@TiH2 core–shell microstructure formed spontaneously, in which the TiH2 core acts as an electron transfer pathway and the shell functioned as the polysulfide absorber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Considering these merits of metal hydrides, we believe that they are promising electrocatalysts to functionalize the separators of Li–S batteries. However, most of the reported metal hydrides are mainly in the bulk form and it is difficult to obtain nanostructured metal hydrides, which makes it difficult to fully exploit the corresponding surface chemical reactivity and catalytic activity. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering these merits of metal hydrides, we believe that they are promising electrocatalysts to functionalize the separators of Li–S batteries. However, most of the reported metal hydrides are mainly in the bulk form and it is difficult to obtain nanostructured metal hydrides, which makes it difficult to fully exploit the corresponding surface chemical reactivity and catalytic activity. , …”
Section: Introductionmentioning
confidence: 99%
“…However, most of the reported metal hydrides are mainly in the bulk form and it is difficult to obtain nanostructured metal hydrides, which makes it difficult to fully exploit the corresponding surface chemical reactivity and catalytic activity. 32,33 Herein, we report a facile liquid-phase exfoliation strategy for scalable production of TiH 2 nanodots (THNDs) as efficient LiPSs immobilizers and bifunctional electrocatalysts for functional separators of Li−S batteries. Based on the experimental and theoretical investigations, we found that THNDs can effectively immobilize the LiPSs through strong anchoring capability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, the slope of the fitting line could be applied to further evaluate the diffusion coefficient (D Li + ) in S cathodes according to the Randles-Sevick equation. 68,69 For the PIL@Li8c-PIL@S and Li8S batteries, the slopes of fitting lines are 11.04 and 9.15 for peak A, 4.95 and 4.36 for peak B, 7.39 and 5.15 for peak C, respectively. From the slopes, D Li + ratio can be calculated to be 1.21, 1.14 and 1.43, suggesting that Li migrates much faster in the c-PIL@S cathode.…”
Section: Materials Advances Papermentioning
confidence: 99%